The Wireless Air Quality Monitoring System - Mohamad Nur Sulin, NurFatihah Fatin; Abdul Sukor, Prof. Madya Ts. Dr. Jumadi (Progress in Engineering Application and Technology, 2021)
This project is to develop a low cost, mobile Air Pollutant Index (API) Monitoring System, which consists of Air Quality Sensor (MQ135 as a sensor detecting gas, Node MCU Esp8266, BME280 as a pressure humidity sensor and concentration sensor. Readings from the sensor has been compared with reference data from the Department of Environment, Malaysia to ensure the results validity of the developed system. The developed dust detector is expected to provide a relatively accurate API reading and suitable to be used for the detection and monitoring of dust concentrations for normal areas around Parit Samsu,Muar Johor.